No Intersection between Line and Ellipse

The line y = mx + c does not intersects the ellipse \frac{{{x^2}}}{{{a^2}}} +  \frac{{{y^2}}}{{{b^2}}} = 1, so the condition for no intersection is that {c^2} < {a^2}{m^2} + {b^2}.
Consider the equation of a line is represented by

y =  mx + c\,\,\,{\text{ -  -  - }}\left( {\text{i}} \right)


Consider the standard equation of ellipse with vertex at origin \left( {0,0}  \right)can be written as

\frac{{{x^2}}}{{{a^2}}}  + \frac{{{y^2}}}{{{b^2}}} = 1\,\,\,{\text{ -   -  - }}\left( {{\text{ii}}}  \right)


To find the point of intersection of straight line (i) and the given ellipse (ii), using the method of solving simultaneous equation we solve equation (i) and equation (ii). Putting the value of y from equation (i) in equation (ii), we have

\begin{gathered} \frac{{{x^2}}}{{{a^2}}} + \frac{{{{\left( {mx  + c} \right)}^2}}}{{{b^2}}} = 1 \\ \Rightarrow \frac{{{b^2}{x^2} +  {a^2}{{\left( {mx + c} \right)}^2}}}{{{a^2}{b^2}}} = 1 \\ \Rightarrow {b^2}{x^2} + {a^2}{\left( {mx +  c} \right)^2} = {a^2}{b^2} \\ \Rightarrow {b^2}{x^2} + {a^2}\left(  {{m^2}{x^2} + 2mcx + {c^2}} \right) = {a^2}{b^2} \\ \Rightarrow {b^2}{x^2} + {a^2}{m^2}{x^2} +  2{a^2}mcx + {a^2}{c^2} - {a^2}{b^2} = 0 \\ \Rightarrow \left( {{a^2}{m^2} + {b^2}}  \right){x^2} + 2{a^2}mcx + {a^2}\left( {{c^2} - {b^2}} \right) = 0\,\,\,{\text{  -  -   - }}\left( {{\text{iii}}} \right) \\ \end{gathered}



no-intersection-line-ellipse

Since equation (iii) is a quadratic equation in x and can have at most two roots. This shows that the line (i) can intersect the ellipse (ii) at most two points. It is also clear from the given diagram. If equation (iii) has imaginary roots, then the line (i) will not intersect the ellipse (ii) as shown in the given diagram
For Imaginary roots, we have

\begin{gathered} {\text{Discriminant  <   0}} \\ \Rightarrow {\left( {2{a^2}mc} \right)^2} -  4\left( {{a^2}{m^2} + {b^2}} \right){a^2}\left( {{c^2} - {b^2}} \right) < 0 \\ \Rightarrow 4{a^4}{m^2}{c^2} - 4{a^2}\left(  {{a^2}{m^2} + {b^2}} \right)\left( {{c^2} - {b^2}} \right) < 0 \\ \Rightarrow {a^2}{m^2}{c^2} - \left(  {{a^2}{m^2} + {b^2}} \right)\left( {{c^2} - {b^2}} \right) < 0 \\ \Rightarrow   - {b^2}{c^2} + {a^2}{m^2}{b^2} + {b^4} < 0 \\ \Rightarrow {c^2} - {a^2}{m^2} - {b^2} <  0 \\ \Rightarrow \boxed{{c^2} < {a^2}{m^2} +  {b^2}} \\ \end{gathered}

Comments

comments

Posted in: